The arch-conjuror of England : John Dee - Parry, G. J. R. (Yale University Press, 2011)
Outlandish alchemist and magician, political intelligencer, apocalyptic prophet, and converser with angels, John Dee (1527-1609) was one of the most colorful and controversial figures of the Tudor world. In this fascinating book -- the first full-length biography of Dee based on primary historical sources -- Glyn Parry explores Deeʹs vast array of political, magical, and scientific writings and finds that they cast significant new light on policy struggles in the Elizabethan court, conservative attacks on magic, and Europe's religious wars. John Dee was more than just a fringe magus, Parry shows: he was a major figure of the Reformation and Renaissance. -- Publisher.